Study Of Query Optimization For XML Databases - Haw, Su Cheng (2008)
This study adressess the problem of structural query processing for various types of queries ranging from simple path query to complex query in native XML databases. We propose theree hybrid systems, i.e., INLAB, INLAB2 and TwiqX-Guide combining indexing and labeling technologies to accelerate twiq query processing based on a decomposition-matching-merging algorithm.